A novel isoform of the Ly108 gene ameliorates murine lupus - Keszei, Marton (The Rockefeller University Press, 2011)
Studies of human systemic lupus erythematosus patients and of murine congenic mouse strains associate genes in a DNA segment on chromosome 1 with a genetic predisposition for this disease. The systematic analysis of lupus-prone congenic mouse strains suggests a role for two isoforms of the Ly108 receptor in the pathogenesis of the disease. In this study, we demonstrate that Ly108 is involved in the pathogenesis of lupus-related autoimmunity in mice. More importantly, we identified a third protein isoform, Ly108-H1, which is absent in two lupus-prone congenic animals. Introduction of an Ly108-H1–expressing transgene markedly diminishes T cell–dependent autoimmunity in congenic B6.Sle1b mice. Thus, an immune response–suppressing isoform of Ly108 can regulate the pathogenesis of lupus.